Target Retirement Fund - Shoven, John B.,Walton, Daniel (National Bureau of Economic Research, 2023)
This paper evaluates a new variant of the popular target date funds used in employer-based retirement savings plans. We call this new variant a
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Betriebliche Altersversorgung; Pensionskasse; Portfolio-Management; Leibrente; Altersgrenze; Altersvorsorge; USA; Portfolio Choice; Investment Decisions; Insurance; Insurance Companies; Actuarial Studies; Economics of the Elderly; Economics of the Handicapped; Non-Labor Market Discrimination; Retirement; Retirement Policies